Two new genera of Agathidinae (Hymenoptera: Braconidae) with a key to the genera of the New World - Sharkey, Michael (Zootaxa, 2006)
Two new genera of Agathidinae (Hymenoptera: Braconidae) are described, Amputoearinus Sharkey n. gen., and Austroearinus Sharkey n. gen. Biological information is given for members of both genera. Five new species are described, Amputoearinus matamata Sharkey n. sp., Amputoearinus fernandezi Sharkey n. sp., Austroearinus chrysokeras Sharkey n. sp., and Austroearinus melanopodes Sharkey n. sp. Two new combinations are made, Austroearinus rufofemoratus n. comb., Austroearinus unicolor (Schrottkey) n. comb. A key to the genera of the New World is presented.